Proceedings of the 2016 CHI Conference on Human Factors in Computing Systems 2016
DOI: 10.1145/2858036.2858234
|View full text |Cite
|
Sign up to set email alerts
|

Social Media Image Analysis for Public Health

Abstract: Several projects have shown the feasibility to use textual social media data to track public health concerns, such as temporal influenza patterns or geographical obesity patterns. In this paper, we look at whether geo-tagged images from Instagram also provide a viable data source. Especially for "lifestyle" diseases, such as obesity, drinking or smoking, images of social gatherings could provide information that is not necessarily shared in, say, tweets. In this study, we explore whether (i) tags provided by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(44 citation statements)
references
References 23 publications
0
42
0
2
Order By: Relevance
“…A linguistic analysis [15] of Twitter activity found Twitter-derived statistics can improve predictive accuracy for some health-related statistics at county level. User-provided and machine-generated geo-tags of images from Instagram can also be used to infer a county's health statistics, such as obesity statistics [22]. Paul & Dredze [48] applied a topic model to health-related tweets and discovered quantitative correlations with public health data.…”
Section: Social Media and Public Healthmentioning
confidence: 99%
“…A linguistic analysis [15] of Twitter activity found Twitter-derived statistics can improve predictive accuracy for some health-related statistics at county level. User-provided and machine-generated geo-tags of images from Instagram can also be used to infer a county's health statistics, such as obesity statistics [22]. Paul & Dredze [48] applied a topic model to health-related tweets and discovered quantitative correlations with public health data.…”
Section: Social Media and Public Healthmentioning
confidence: 99%
“…The only previous work we are aware of that used automatically extracted image tags is [21], which found that image tags were predictive of lifestyle factors; for example, "glass", "liquid" and "beverage" were associated with excessive drinking. The authors suggested that image tags may be useful for identifying stigmatizing behaviors, where social media users may post images of an activity but not tag the activity in an explicit way.…”
Section: Discussionmentioning
confidence: 99%
“…A few studies have looked at substance use on Instagram, including electronic cigarettes [18], marijuana [19], and opioids [20]. Garimella et al [21] looked more broadly at lifestyle choices in Instagram, including diet, physical activity, and drinking. Notably, this study used both text features and image features, which also we do in our study.…”
Section: Prior Workmentioning
confidence: 99%
“…For instance, Wagner et al [54] analyzed data from an online recipe platform to understand the association between geographic proximity and shared dietary preferences and the extent to which temporal information helps to predict these preferences. Twitter and Facebook posts [1] as well as the content of Instagram images [23] have further been found to correlate with CDC reported prevalence of obesity in different geographical regions, as well as in helping infer caloric and nutrient consumption. Weber and Mejova [58], recently showed the feasibility of using crowd-sourcing to infer body weight categories from profile pictures shared on Twitter.…”
Section: Related Workmentioning
confidence: 99%